Incidence Rates and Impact of Ventilator-Associated Patients in Pediatric Intensive Care Unit Chiang Mai University Hospital - Kaphan, Kraiwan; Muangcom, Supanee (Biomedical Sciences and Clinical Medicine, 2024)
Objective To determine the incidence and the impacts of ventilator-associated pneumonia (VAP) in patients admitted to Pediatric Intensive Care Unit (PICU), Chiang Mai University Hospital. Methods This was a retrospective study of patients age between 1 month and 15 years, admitted to PICU, Chiang Mai University Hospital, during October 1, 2013 to September 30, 2014, who needed mechanical ventilator more than 48 hours. VAP was diagnosed using the definition from the Centers for Disease Control and Prevention (CDC), USA. Hospital records were reviewed and analyzed using the Statistic Package for the Social Science (SPSS) for Windows. Results One hundred and fifty six patients met the inclusion criteria. Fourteen patients developed VAP. The VAP incidence rate was 7.9 per 1,000 ventilator-days. The most common pathogen causing VAP was Acinetobactor baumanii (35.7%). The median of length of ventilator days and intensive care unit stay were 22.5 days and 39.0 days respectively. The mortality rate of VAP was 3.8 per 100 mechanically ventilated patients. Case fatally rate was 42.9 per 100 VAP patients. The median cost was 1,023,949.00 Baths per case. Conclusion VAP caused serious impacts and economic burden. Hospital personnel taking care of mechanically ventilated patients should realize these impacts and strictly follow VAP prevention guideline